Pengenalan Software Akuntansi Buku Warung untuk Kelompok UMKM dan PKK di Desa Iwul Kecamatan Parung Kabupaten Bogor - Dicky, Muhamad; Noviani, Witria; Supandi, Yusuf; Ananda, Zakaria; Suripto, Suripto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This community service aims to analyze and contribute ideas regarding motivation and creativity in independent small businesses in Lengkong Barang village RT.001/003 Iwul-Parung Village, Bogor. Where MSMEs have a very important role in the development and growth of the Indonesian economy. The current phenomenon of the Industrial Revolution 4.0 has had a major impact on human civilization. This impact is felt not only in developed countries, but also in other developing countries. The method used is a descriptive method in delivering material directly through discussions/interviews regarding financial planning using applications. The conclusion of this community service is that assistance will be provided in recording through the BukuWarung application for the development of independent business actors and PKK groups in an effort to realize community welfare in Iwul-Parung Village, Bogor.